Legal Review of Legal Protection for Children Born Out of Wedlock Based on Constitutional Court Decision Number 46/PUU-VIII/2010: Implications of Constitutional Court Decision No. 46/PUU-VIII/2010 on the Rights of Children Born Out of Wedlock - Elis Yesika br Rajagukguk; Roida Nababan; Sovia Simamora (International Journal of Law, Crime and Justice, 2025)
This research examines the legal safeguards for children born outside of marriage in Indonesia after the release of Constitutional Court Decision (MK) No. 46/PUU-VIII/2010, which represented a pivotal shift in national family legislation. Up until now, children born outside of marriage have frequently encountered bias and unfair treatment, both socially and legally. The Constitutional Court (MK) Decision No. 46/PUU-VIII/2010 marks an important advancement in enhancing the civil status of children born outside of marriage, establishing connections not just with their mother and her relatives, but also with their biological father if scientifically validated, for instance, via DNA testing. In this research, the author will examine how judges define legal protection for children born outside of marriage in light of Constitutional Court Decision No. 46/PUU-VIII/2010 and how this decision is executed in legal practices and everyday life, especially concerning the acknowledgment of rights for children born outside of marriage and the obligations of their biological fathers.This study uses a normative research method with a legislative approach and a case approach.  Data was collected through library research covering primary, secondary, and tertiary legal materials, namely by collecting legal materials through studies of books, journals, legal research results,  as well as various official institutional documents such as regulations and other literature relevant to the issues being studied.  The research findings indicate that legal protection for children born out of wedlock needs to be further strengthened through legal reform, public education,  and legal recognition and validation mechanisms, so that the basic rights of children can be optimally fulfilled in accordance with human rights principles and applicable laws and regulations.